The Phenomenon of Kampung in Surabaya in Defensible Space Perspective: Case Study on Kampung Tambaksari Surabaya - Tri Widyastuti (Direktorat Riset dan Pengabdian Kepada Masyarakat, 2023)
Kampungs, simple settlement units commonly found in Indonesian cities,including Surabaya, play a significant role in the city's development,preserving its identity as a metropolitan city with a strong foundation rootedin these traditional communities. Surabaya recognizes the importance ofkampungs and their contribution, evident from the existence of around 5000kampungs within the city. However, being a bustling metropolitan center,Surabaya also faces its fair share of crime-related challenges. One theory thataddresses the relationship between crime and the built environment is thedefensible space theory. To explore this further, a study examines Tambaksari,a kampung within Surabaya, in the context of the current defensible spacetheory. This investigation employs an in-depth observation method to gatherspecific data on Tambaksari as a single case, aiming to provide valuableinsights for stakeholders to formulate more targeted policies that enhance thedevelopment of kampungs in Surabaya while effectively addressing crimerelated issues.